2017
DOI: 10.1016/j.devcel.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Kibra and Merlin Activate the Hippo Pathway Spatially Distinct from and Independent of Expanded

Abstract: SUMMARY The Hippo pathway is emerging as a key evolutionarily conserved signaling mechanism that controls organ size. Three membrane-associated proteins, Kibra, Merlin, and Expanded regulate pathway activity, but the precise molecular mechanism by which they function is still poorly understood. Here we provide evidence that Merlin and Kibra activate Hippo signaling in parallel to Expanded at a spatially distinct cellular domain, the medial apical cortex. Merlin and Kibra together recruit the adapter protein Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 42 publications
4
110
2
1
Order By: Relevance
“…It was further suggested that aPKC phosphorylates the Crb FERM-binding domain (Sotillos et al, 2004) and that this domain might contribute to stabilization of Crb at the apical domain (Fletcher et al, 2012). Further genetic and structural evidence supports a key role for direct interaction with Sdt/PALS1 in maintaining endogenous Crb at the plasma membrane by preventing Crb endocytosis (Ivanova et al, 2015;Li et al, 2014;Lin et al, 2015) and that aPKC phosphorylation of Crb may antagonize Moe binding in favour of Ex (Sherrard and Fehon, 2015b;Su et al, 2017) or Sdt (Wei et al, 2015). However, recent evidence indicates that deletion of the extracellular domain of endogenously expressed Crb, or mutation of the FERM binding domain of endogenously expressed Crb, does not disrupt epithelial polarity during embryonic gastrulation in Drosophila (Cao et al, 2017;Das and Knust, 2018;Klose et al, 2013), although it can affect Crb localization in the follicle cell epithelium (Sherrard and Fehon, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…It was further suggested that aPKC phosphorylates the Crb FERM-binding domain (Sotillos et al, 2004) and that this domain might contribute to stabilization of Crb at the apical domain (Fletcher et al, 2012). Further genetic and structural evidence supports a key role for direct interaction with Sdt/PALS1 in maintaining endogenous Crb at the plasma membrane by preventing Crb endocytosis (Ivanova et al, 2015;Li et al, 2014;Lin et al, 2015) and that aPKC phosphorylation of Crb may antagonize Moe binding in favour of Ex (Sherrard and Fehon, 2015b;Su et al, 2017) or Sdt (Wei et al, 2015). However, recent evidence indicates that deletion of the extracellular domain of endogenously expressed Crb, or mutation of the FERM binding domain of endogenously expressed Crb, does not disrupt epithelial polarity during embryonic gastrulation in Drosophila (Cao et al, 2017;Das and Knust, 2018;Klose et al, 2013), although it can affect Crb localization in the follicle cell epithelium (Sherrard and Fehon, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , Echinoid, an IgCAM member, has been shown to facilitate Hippo (MST1/2 in mammals) activation and subsequent Yorkie (YAP1) phosphorylation by interacting with multiple components of the Hippo pathway, including the scaffold proteins Salvador (SAV1), Merlin (NF2), Expanded (FRMD6) and KIBRA . Salvador (SAV1) is a key molecule among these scaffold proteins; SAV1 localizes to the cell membrane through an interaction with Echinoid, and then recruits Hippo to the cell‐cell junction . Merlin directly binds and recruits Warts (LATS1/2) to the plasma membrane, while membrane recruitment promotes Warts phosphorylation by the Hippo‐Salvador kinase complex .…”
Section: Discussionmentioning
confidence: 99%
“…and then recruits Hippo to the cell-cell junction. 24 Merlin directly binds and recruits Warts (LATS1/2) to the plasma membrane, while membrane recruitment promotes Warts phosphorylation by the Hippo-Salvador kinase complex. 22 In the present study, we found that CADM1 formed complexes with multiple Hippo pathway core 50).…”
Section: Disease-free Survival Curves Based On Expression Patterns mentioning
confidence: 99%
“…Yap/Yorkie is an important mechanosensitive regulator of cell cycle (Dupont et al, 2011;Huang et al, 2005). To address whether in addition to E2F1, BAF also represses Yap/Yorkie, we used a YFP-tagged version of Yorkie expressed under its endogenous promoter (Yki-YFP), shown previously to rescue yki mutants (Su et al, 2017), to follow Yorkie subcellular distribution in muscles. Staining of control larval muscles with anti GFP antibody (which recognizes YFP), indicated homogenous distribution of Yki-YFP within the muscle with no accumulation in the myonuclei.…”
Section: Baf Represses the Accumulation Of Yap/yorkie In The Myonucleimentioning
confidence: 99%
“…The following stocks were distributed by the Bloomington Drosophila Stock Center: tubP- were combined on Cyo-YFP and TM6Tb balancers, koi 84 (FBst0025105)/Cyo-dfd-eYfp (Kracklauer et al, 2007). Yorkie-YFP (R. Fehon, University of Chicago (Su et al, 2017).…”
Section: Fly Stocks and Husbandrymentioning
confidence: 99%